Integrated physical training in combat sports - Raquel Hernández García; Gema Torres Luque (Federación Extremeña de Balonmano; University of Extremadura, 2011)
Abstract This paper aims to define the concepts of embedded training (EI) and integrated fitness (PFI) and the importance of these concepts have in training in combat sports. And define a set of guidelines and examples of PFI in the combat sport of judo. Key words: integrated training, integrated physical training, combat sports, judo